Levodopa Equivalent Daily Dosage: Geographical Variations and Real-Life Modules in Parkinson's Disease - Kukkle, Prashanth Lingappa; Kalia, Lorraine V; Habib, Ahsan; Jagota, Priya; Ojha, Rajeev; Kandadai, Rukmini Mridula; Desai, Soaham; Caldera, Manjula; Sirisena, Darshana; Garg, Divyani; Mestre, Tiago A; Neupane, Rosy; et al. (Movement disorders clinical practice (Hoboken, N.J.), 2024)
The Levodopa Equivalent Daily Dosage (LEDD) calculation algorithms help in capturing and harmonization of Parkinson's Disease (PD) therapies. Analyzing these updates is essential for validating their effectiveness. To assess updated LEDD conversion factors in capturing the newer therapies in PD and therapy modules in different geographical cohorts. Data were sourced from 10 Centers from 6 countries representing 2 different continents. The study compared the LEDD conversion factors proposed by Tomlinson et al and Jost et al, alongside investigating demographic disparities. The analysis involved 2943 subjects; 87% (n = 2577) met the UK Brain Bank criteria for PD. The LEDD differed significantly across methodologies (Tomlinson vs. Jost, 598 mg vs 610 mg, P < 0.0001). Geographical disparities highlighted variations in PD onset age (P < 0.0001). Jost and Tomlinson's calculations demonstrated consistency within but significant differences across countries (P < 0.0001).Age at onset revealed statistically significant differences in LEDD requirements (P < 0.0001), which were particularly higher in 21-50 years (718 mg vs 566 mg). This subgroup also demonstrated increased usage of non-Levodopa therapies (P < 0.0001). Men exhibited higher total LEDD (P = 0.001). 34% reported dyskinesia, associated with higher LEDD (756 mg, P < 0.0001). Surgically treated patients also had higher LEDD (P < 0.0001) and a significant difference between Jost and Tomlinson dosages (761 mg vs716mg) reflecting the incorporation of newer therapeutic molecules. This analysis delineates the importance of updated LEDD algorithms and intricacies in the landscape of PD treatment, underscored by geographical, age-related, and gender-specific variations, in real-life management scenarios.